Simulated awareness. Some critical thoughts on disability simulations - Albin, Kamila (Understanding Disability: Issues, Research, Reflections, 2021)
This paper gives critical consideration to the so-called disability simulations, a widespread practice during disability awareness trainings, conducted in different age groups: for students of primary schools, high schools, administrative staff, cultural institutions, etc. It is commonly believed that „embodiment” into a person with disabilities can have a positive impact on attitudes towards people with disabilities. On the other hand, some activists and researchers claim that such disability simulations can reinforce prejudices and negative stereotypes, portraying disability as an individual experience and personal tragedy. This stands against the notion of the social model of disability. Using an autoethnographic perspective, the author, basing herself, among other things, on her own experience as a trainer, analyses the practice of disability simulations trainings. The aim of the analysis is not only to take a critical look at what is becoming a common method of teaching about disability, but also to look for alternatives that promote social understanding of disability.